Current trends and issues in Indian federalism - Jha, Prakash Chandra (Indian Journal of Public Administration)
The article examines the recent trends and issues in Indian federalism. The federal system has become transformedy in the last seven decades$1 (Bfrom being dismissed as a full-fledged federal system to a widely acclaimed federal system in the world. Simply put, Indian federalism has become more meaningful and functional post-liberalisation. The article has examined this turnaround. From a subordinate position till the late 1980s, states rose to occupy a strategic position in India$1 (Bs move from a command economy to a market economy. No wonder, therefore, the Centre became more interested in involving states in even forbidden area such as foreign policy matters. Divisive politics in several states today is being replaced by developmental politics. States are not only competing but also learning from each other. States are being seen by the Centre as drivers of India$1 (Bs growth. - Reproduced.s